ANALISIS SPASIAL UNTUK PERENCANAAN JALAN TAMBANG DENGAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS: SPATIAL ANALYSIS FOR MINE ROAD PLANNING USING THE ANALYTICAL HIERARCHY PROCESS METHOD - Eric Arung Patandianan (Universitas Papua, 2014)
Feasibility exploration of geological resources is not only seen by the quality and reserves, but also one of the important factor is access to transportation. This paper aims to plan a safe and low cost mine road using by AHP method and image analysis. The results of the analysis of mine road planning at the mine site to the port in total within ± 71.950 meters with land clearing for new road along the ± 22.061 meters with a single across the river, clearing bushes along the ± 20.733 meters and clearing forest along the ± 1.328 meters as well as on some point of mine road planning maximum slope of the cutting by 10% and 30%, so that the necessary evaluation in these areas.